Chlorella sp. Cultivation Using Parboiled Rice Efuent and Utilization of the Microalgae as Co‑organic Fertilizer for Brinjal (Solanum melongina) - Hetti Gamage, L.R.K.; Nalina, G.; Ketheesan, B.; Kasthuri, K. (Springer, 2023)
Abstract Purpose Chlorella sp. was cultivated in the parboiled rice efuent without any other nutrient supplement and the potential of the biomass as organic fertilizer in combination with organic or inorganic fertilizers was studied. Methods Chlorella sp. was cultivated in a raceway reactor for 14 days in parboiled efuent. A pot experiment with Brinjal (Solanum melongina) was conducted with combinations of either 50% organic (cow manure) or 50% inorganic fertilizer with Chlorella soil application or foliar application, sole organic or inorganic and control. An incubation experiment was also planned in parallel to measure the soil available nutrients. The growth and yield parameters in pot experiment were measured at regular intervals. Results The incubation study revealed that Chlorella at 3 g kg−1 gave similar available nitrogen as inorganic fertilizer, while improving available phosphorus and potassium. All the combination treatments of Chlorella gave similar or higher pod yield than the sole inorganic fertilizer treatment except the control. Conclusion This study therefore, highlights the potential of Chlorella sp. grown in parboiled efuent as a complementary organic fertilizer.